Duplex Ultrasound of Superficial Leg Veins - Mendoza, Erika; Lattimer, Christopher R.; Morrison, Nick (Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book describes in detail the use of duplex ultrasound for exploration of the superficial veins and their pathology. It has a practical orientation, presenting numerous clinical situations and explaining how to identify the different sources of reflux, specially in the groin. The investigation of pathology of the saphenous trunks, perforators, and side branches is described in detail. As duplex ultrasound plays an important role during various venous surgical procedures, its application pre-, intra-, and postoperatively is presented. Furthermore, the sonographic appearances of thrombotic pathology of superficial and deep veins, edema, and other conditions that may be observed while exploring the veins are fully described. The book is based on the authors' extensive clinical experience and is intended to assist fellow practitioners who want to learn more about the technique. It includes a wealth of informative images with the aim of covering every potential situation.